Zintegrowanie społeczności przedszkolnej wokół patrona - Łukaszewska, Anna Łukaszewska (Studia Edukacyjne, 2024)
Polish educational law provides the opportunity for the preschool community to choose a patron. This is usually a deceased person, who is an inspiration in pedagogical work and a role model. Recurring events and ceremonies related to the patron create preschool traditions, which integrate the preschool community. These events are an excellent way to foster social skills and strengthen intergenerational bonds. This article reviews the best practices based on selected municipal preschools in Toruń, demonstrating the importance of the patron in the life of the preschool. The author emphasizes the cooperation between the preschool and the child’s family environment, crucial for the social development of the preschool child. The final conclusions and recommendations help outline the development path of preschool education.